Determinants of Facility-Based Childbirth in Indonesia - Ferry Efendi; Ani Rihlatun Ni’mah; Setho Hadisuyatmana; Heri Kuswanto; Linlin Lindayani; Sarni Maniar Berliana (The Scientific World Journal)
Background. Reducing maternal mortality remains a significant challenge in Indonesia, especially for achieving the country’s Sustainable Development Goals (SDGs) by 2030. One of the challenges is increasing delivery at healthcare facilities to ensure safe and healthy births. In Indonesia, research on factors affecting women’s use of facility-based childbirth services is scarce. Objective. This study was conducted to identify the determinants of facility-based deliveries in Indonesia. Methods. This study used data from the Indonesia Demographic and Health Survey of 2012, with a cross-sectional design. An odds ratio with 95% confidence intervals (CI) was employed to outline the independent variables for the determinants, including maternal age and education, place of residence, involvement in decision-making, employment status, economic status, and number of antenatal care visits. The dependent variable in this study was the place of delivery: whether it took place in healthcare or nonhealthcare facilities. The statistical significance was set at p<0.05 using bivariate analysis and binary logistic regression. Results. This study showed that a high level of education (OR: 3.035, 95% CI: 2.310–3.987), high economic status (OR: 6.691, 95% CI: 5.768–7.761), urban residence (OR: 2.947, 95% CI: 2.730–3.181), working status (OR: 0.853, 95% CI: 0.793–0.918), involvement in decision-making (OR: 0.887, 95% CI: 0.804–0.910), and having more than four visits to antenatal care centers (OR: 1.917, 95% CI: 1.783–2.061) were significant determinants of delivery at healthcare facilities. Conclusion. Efforts to improve facility-based childbirth in Indonesia must strengthen initiatives that promote women’s education, women’s autonomy, opportunities for wealth creation, and increased uptake of antenatal care, among others. Any barriers related to maternal healthcare services and cultural factors on the use of health facilities for childbirth in Indonesia require further monitoring and evaluation.